Stress acts cumulatively to precipitate Alzheimer's disease-like Tau pathology and cognitive deficits - Sotiropoulos, Ioannis; Pollerberg, G. Elizabeth (The journal of neuroscience, 2011)
Stressful life experiences are likely etiological factors in sporadic forms of Alzheimer's disease (AD). Many AD patients hypersecrete glucocorticoids (GCs), and their GC levels correlate with the rate of cognitive impairment and extent of neuronal atrophy. Severity of cognitive deficits in AD correlates strongly with levels of hyperphosphorylated forms of the cytoskeletal protein TAU, an essential mediator of the actions of amyloid β (Aβ), another molecule with a key pathogenic role in AD. Our objective was to investigate the sequential interrelationships between these various pathogenic elements, in particular with respect to the mechanisms through which stress might precipitate cognitive decline. We thus examined whether stress, through the mediation of GCs, influences TAU hyperphosphorylation, a critical and early event in the cascade of processes leading to AD pathology. Results from healthy, wild-type, middle-aged rats show that chronic stress and GC induce abnormal hyperphosphorylation of TAU in the hippocampus and prefrontal cortex (PFC), with contemporaneous impairments of hippocampus- and PFC-dependent behaviors. Exogenous GC potentiated the ability of centrally infused Aβ to induce hyperphosphorylation of TAU epitopes associated with AD and cytoplasmic accumulation of TAU, while previous exposure to stress aggravated the biochemical and behavioral effects of GC in Aβ-infused animals. Thus, lifetime stress/GC exposure may have a cumulative impact on the onset and progress of AD pathology, with TAU hyperphosphorylation serving to transduce the negative effects of stress and GC on cognition.